PEMBANGUNAN WILAYAH KECAMATAN BERBASIS KOMODITI PERTANIAN DI KABUPATEN BOYOLALI (PENDEKATAN SHIFT-SHARE ANALISIS) - Ropingi Ropingi; Agustono Agustono (Sepa, 2021)
The aimed of this reserach are: (1) Knowing agriculture commodity becoming bases at each district in Boyolali egency; (2) Knowing component growth of agriculture commodity in each district in Boyolali Regency; (3) Knowing agriculture commodity development priority i every district in Boyolali Regency . Needed by Data was data produce agriculture commodity every district in Boyolali Regency year 2004 and 2005, agriculture commodity price data year 2004 and 2005 and regional generality data Boyolali Regency. The data obtained from Statistical center Council (bps) Central java Province, Statistical Center Council (BPS) Boyolali Regency, and Agriculture Departement of Boyolali Regency